An aggregation-induced emission platform for efficient Golgi apparatus and endoplasmic reticulum specific imaging. Issue 41 (11th October 2021) - Xiao, Peihong; Ma, Ke; Kang, Miaomiao; Huang, Luyi; Wu, Qian; Song, Nan; Ge, Jinyin; Li, Dan; Dong, Jianxia; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract : As two important subcellular organelles in eukaryotic cells, the Golgi apparatus (GA) and endoplasmic reticulum (ER) have recently captivated much interest due to their considerable importance in many biofunctions and role as critical biomarkers for various diseases. Abstract : As two important subcellular organelles in eukaryotic cells, the Golgi apparatus (GA) and endoplasmic reticulum (ER) have recently captivated much interest due to their considerable importance in many biofunctions and role as critical biomarkers for various diseases. The development of efficient GA- and ER-specific probes is of great significance, but remains an appealing yet significantly challenging task. Herein, we reported for the first time the construction of an aggregation-induced emission (AIE) platform for GA and ER fluorescent probes, termed as AIE-GA and AIE-ER, by facile synthesis and simple functionalization. Their excellent targeting specificity to GA or ER, remarkable photostability, high brightness, and low working concentration make AIE-GA and AIE-ER significantly impressive and superior to commercially available probes. Moreover, molecular docking calculations are performed to validate the targeting mechanism of the two AIE probes.